MODELING AND SIMULATION OF PROLATE DUAL-SPIN SATELLITE DYNAMICS IN AN INCLINED ELLIPTICAL ORBIT : CASE STUDY OF PALAPA B2R SATELLITE - Muliadi, J.; Jenie, Said D.; Budiyono, A. (Indonesian Journal of Aerospace, 2005)
In response to the interest to re-use PAlapa B2R satellite nearing its End of Life (EOL) time, an idea to incline the satellite orbit in order to cover a new region has emerged in the recent years. As a prolate dual-spin vehicle, Palapa B2R has to be stabilized against its internal energy dissipation effect. This work is focused on analyzing the dynamics of the reusable satellite in its inclined orbit. The study discusses in particular the stability of the prolate dual-spin satellite in the effect of pertubed field of gravity due to the inclination of its elliptical orbit. Palapa B2R physical data was substituted into the dual-spin's equation of motion. The coefficient of zonal harmonics J2 was induced into the gravity-gradient moment term that affects the satellite attitude. The satellites's motion and attitude were then simulated in the pertubed gravitational field by J2 with the variation of orbit's eccentricity and inclination. The analysis of the satellite dynamics and its stability was conducted for designing control system for the vehicle in its new inclined orbit.